The Impact of Rural Hospital Closures on Emergency Medical Services Transport Times - Todd Brenton Smith; Thomas MacAndrew English; Marilyn Whitman; Dwight Lewis; Abbey Gregg (Rural Nurse Organization; Binghamton University, 2022)
Purpose: Previous studies have found disparities in emergency medical service (EMS) transports for rural residents including double the average response time and lower patient survival rates when compared with their urban counterparts. Since 2012, the rate of rural hospitals closures has risen alarmingly from previous years. Previous studies have linked the closure of rural hospitals to increased EMS transport and total activation time. However, data and methods used in previous studies have not included facility-level characteristics, which limits the ability to tease out the nuances of each closure. Thus, the purpose of this study is to examine the impact of rural hospital closures on EMS travel time, as well as the characteristics of the closed hospitals. Sample: Data sources for the study came from a state-level EMS database, the CMS Provider of Service files, and state-level hospital data reports.  Methods: Geographic information system software was used to geocode hospital locations and generate service areas based on drive times. We identified rural hospitals that closed in Alabama between 2010-2018 and then identified the 911 call data from the state's EMS database that occurred within close proximity of each of the hospitals of interest, resulting in a sample of 120,802 EMS calls. Findings: We identified five hospital closures within our time period.  For one of the five closures, EMS transport time to the emergency department increased by thirteen minutes post-closure. In two of the five closures, transport time increased by five minutes or less. In two instances, however, transport time decreased. Conclusions: Our findings suggest that not all rural hospital closures result in increased EMS transport times as rural patients may have already been routinely transported to alternate hospitals.  Additionally, specific characteristics of a hospital pre-closure may be related to changes in EMS travel times that occur post-closure. Keywords: Rural health, emergency medical services, access, hospital closure, travel distance DOI: https://doi.org/10.14574/ojrnhc.v22i1.690